2015
DOI: 10.1089/met.2015.0063
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Sex Steroid Hormones, Lipid Subfractions, and Ectopic Adiposity in Asian Indians

Abstract: Background: Estradiol, testosterone (T), and sex hormone binding globulin (SHBG) levels are associated with lipid subfractions in men and women. Our objective was to determine if associations are independent from adipose tissue area among Asian Indians. Methods: We used data from 42 women and 57 Asian Indian men who did not use exogenous steroids or lipidlowering medications. Lipoprotein subfractions including low-density lipoprotein cholesterol (LDL), very low-density lipoprotein cholesterol (VLDL), and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(37 reference statements)
1
2
0
1
Order By: Relevance
“…For example, the increase in fat levels in the hips and breasts of women is related to estrogen levels. [51] Our mediation MR analysis indeed confirms that the use of HMGCR inhibitor, as lipid-lowering drugs, can lower testosterone levels in men by affecting fat distribution in certain parts of the body (such as arms and feet), and obesity factors also play an important role in this.…”
Section: Discussionsupporting
confidence: 68%
“…For example, the increase in fat levels in the hips and breasts of women is related to estrogen levels. [51] Our mediation MR analysis indeed confirms that the use of HMGCR inhibitor, as lipid-lowering drugs, can lower testosterone levels in men by affecting fat distribution in certain parts of the body (such as arms and feet), and obesity factors also play an important role in this.…”
Section: Discussionsupporting
confidence: 68%
“…SHBG is inversely related to IR via insulin-reducing hepatic SHBG production in in vitro studies (Plymate et al 1988), and associations of cardiovascular risk factors with SHBG may be reflective of SHBG as a potential surrogate marker of insulin resistance. However, lower SHBG was previously associated with a more atherogenic lipid profile consisting of smaller LDL, lower medium LDL and higher triglycerides, VLDL and IDL assessed using ion mobility spectrometry in n = 42 South Asian Indian women (Kim et al 2015) with these findings persisting after adjustment for visceral adiposity and surrogate markers of IR. In keeping with this, in the general population, SHBG is associated with DM2 independent of surrogate measures of IR (Haffner et al 1993, Kalyani et al 2009, and SHBG, but not testosterone, is associated with the prevalence or incidence of subclinical atherosclerosis (Calderon-Margalit et al 2010) in women independent of factors including age, BMI, insulin or clinical lipid measurements.…”
Section: Discussionmentioning
confidence: 92%
“…Xu et al reported that serum E2 and sex hormone binding globulin (SHBG) could influence HbA1c levels in non-diabetic populations [ 50 ]. Kim et al showed that E2, testosterone, and SHBG levels are associated with lipid subfractions in adults [ 51 ]. Similar studies have been conducted in children.…”
Section: Discussionmentioning
confidence: 99%